Adenosine-stress dynamic real-time myocardial perfusion CT and adenosine-stress first-pass dual-energy myocardial perfusion CT for the assessment of acute chest pain: initial results - Weininger, Markus; Fink, Christian; Henzler, Thomas (European journal of radiology, 2012)
Purpose - Recent innovations in CT enable the evolution from mere morphologic imaging to dynamic and functional testing. We describe our initial experience performing myocardial stress perfusion CT in a clinical population with acute chest pain. - Methods and materials - Myocardial stress perfusion CT was performed on twenty consecutive patients (15 men, 5 women; mean age 65±8 years) who presented with acute chest pain and were clinically referred for stress/rest SPECT and cardiac MRI. Prior to CT each patient was randomly assigned either to Group A or to Group B in a consecutive order (10 patients per group). Group A underwent adenosine-stress dynamic real-time myocardial perfusion CT using a novel “shuttle” mode on a 2nd generation dual-source CT. Group B underwent adenosine-stress first-pass dual-energy myocardial perfusion CT using the same CT scanner in dual-energy mode. Two experienced observers visually analyzed all CT perfusion studies. CT findings were compared with MRI and SPECT. - Results - In Group A 149/170 myocardial segments (88%) could be evaluated. Real-time perfusion CT (versus SPECT) had 86% (84%) sensitivity, 98% (92%) specificity, 94% (88%) positive predictive value, and 96% (92%) negative predictive value in comparison with perfusion MRI for the detection of myocardial perfusion defects. In Group B all myocardial segments were available for analysis. Compared with MRI, dual-energy myocardial perfusion CT (versus SPECT) had 93% (94%) sensitivity, 99% (98%) specificity, 92% (88%) positive predictive value, and 96% (94%) negative predictive value for detecting hypoperfused myocardial segments. - Conclusion - Our results suggest the clinical feasibility of myocardial perfusion CT imaging in patients with acute chest pain. Compared to MRI and SPECT both, dynamic real-time perfusion CT and first-pass dual-energy perfusion CT showed good agreement for the detection of myocardial perfusion defects.
Available online 30 December 2010
Gesehen am 06.05.2019